Economies of scale of Malaysian banks - Lim, Pauline (2014)
The purpose of this project is to determine whether there are economies of scale in Malaysian banks. This project is initiated by the increase in competition in the financial sector and the pressing need for banks to curb their expenses. The methodology used is based on Humphrey's studies [1987] where asset cost elasticities (ACE) is used to determine the existence of cost economies. A sample of 72 observations from 17 Malaysian banks for the period 1988-1992 is used for the purpose of this study. The final results obtained are such that there are economies of scale for smaller banks, constant returns to scale for medium-sized banks, and diseconomies of scale for large-sized banks. In other words, the cost curve for banks in Malaysia is U-shaped. The study also suggests that the best bank size to maintain is between RM1,500 million and RM5,000 million.